(untitled) (Eastern Medical College Journal, 2026)
Background: Hirschsprung disease (HD) is a congenital disorder characterized by the absence of ganglion cells at the Meissner’s plexus (submucosa) and Auerbach’s plexus (muscularis) of the terminal rectum that extends in a variable distance proximally. This leads to a lack of gut motility, stool stasis and constipation. Full thickness biopsy is the gold standard for the diagnosis of HD. This study aims to evaluate the efficacy of rectal punch biopsy in the diagnosis of Hirschsprung’s disease. Materials and Methods: This cross-sectional observational study was carried out in the department of pediatric surgery, Mymensingh Medical College Hospital, Mymensingh from January 2018 to April 2019. Sixty (60) cases of clinically, radiologically consistent with Hirschsprung’s disease not in acute stage, chronic constipation with assisted defecation in older children and children who came with colostomy for subsequent management without tissue diagnosis were purposively included in the study. Patients’ information’s were obtained in predesigned questionnaire after obtaining written consent of the parents/guardians in the consent form. All the patients underwent rectal punch biopsy. Study results were expressed as mean ± SD, frequency and percentage. Results: The age range of the study group was 3 days to 7 years with a mean age of 1.20±1.90 years. Most of the patients were in neonatal period (25, 41.66%) followed by infants (18, 30%). Regarding punch biopsy, the adequate sample was 59 (98.31%) and the inadequate sample was only 1 (1.69%). Among adequate tissue material HD 47 cases, non-HD 11 cases and suspicious cases were in 1 case. Only 1 (1.66%) case was presented with hemorrhage after punch biopsy which was later managed. Sensitivity, specificity, Positive predictive value, Negative predictive value and efficiency of the rectal biopsy were 100%, 96.66%, 97.8%, 100% and 98.2% respectively. Conclusion: Rectal punch biopsy is a simple, safe and effective procedure for diagnosing Hirschsprung’s disease, offering high accuracy and a low risk of complications. Eastern Med Coll J. July 2025; 10 (2): 122-126